PHYLOGENOMICS AND PLASTOME EVOLUTION OF THE CHLORIDOID GRASSES (CHLORIDOIDEAE: POACEAE) - Duvall, Melvin R.; Fisher, Amanda E.; Columbus, J. Travis; Ingram, Amanda L.; Wysocki, William P.; Burke, Sean V.; Clark, Lynn G.; Kelchner, Scot A. (International journal of plant sciences, 2016)
Premise of research. Studies of complete plastomes have proven informative for our understanding of the molecular evolution and phylogenomics of grasses, but subfamily Chloridoideae has not been included in this research. In previous multilocus studies, specific deep branches, as in the large clade corresponding to Cynodonteae, are not uniformly well supported. Methodology. In this study, a plastome phylogenomic analysis sampled 14 species representing 4 tribes and 10 genera of Chloridoideae. One species was Sanger sequenced, and 14 other species, including outgroups, were sequenced with next-generation sequencing-by-synthesis methods. Plastomes from next-generation sequences were assembled by de novo methods, and the unambiguously aligned coding and noncoding sequences of the entire plastomes were analyzed phylogenetically. Pivotal results. Complete plastomes showed rare genomic changes in Distichlis, Centropodia, and Eragrostis tef that were of potential phylogenomic significance. Phylogenomic analyses showed uniformly strong support for all ingroup relationships except one node in Cynodonteae in which a short internal branch connected long terminal branches. Resolution within this clade was found to be taxon dependent and possibly subject to long-branch attraction artifacts. Conclusions. Our study indicates that the increase in phylogenetic information in sequences of entire plastomes well resolves and strongly supports relationships among tribes and genera of chloridoid grasses. Sampling more species, especially in the Centropodia + Ellisochloa clade and Cynodonteae, will further address relationships in these groups and clarify the evolutionary origins of the subfamily.